The impact of corporate social responsibilities of corporate social responsibilities implement towards IOI Loders Croklaan Asia employee organization citizenship behavior / Siti Nur Farhana Mohamad - Mohamad, Siti Nur Farhana (2015)
The study aims to identify the implementation of Corporate Social Responsibility Program impact towards IOI Loders Croklaan Asia employee Organizational Citizenship Behavior. It is very important for an organization to ensure that the CSR program implement are beneficial or not to employee organizational citizenship behavior. In this research, the researchers choose four factors which are CSR program to employee, CSR program to customer, CSR program to environment and CSR program to society and government. 398 respondents were chosen from the total population from f 13 departments in the organization by using simple random sampling. The findings of the study are, two independent variables have significant relationship with employee's motivation. The researchers also found CSR program to employee is the most significant predictor variable. Overall, the researchers able to answer all objectives